2009
DOI: 10.1186/1471-2148-9-271
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of Brassica napus FLOWERING LOCUST paralogues in the context of inverted chromosomal duplication blocks

Abstract: BackgroundThe gene FLOWERING LOCUS T (FT) and its orthologues play a central role in the integration of flowering signals within Arabidopsis and other diverse species. Multiple copies of FT, with different cis-intronic sequence, exist and appear to operate harmoniously within polyploid crop species such as Brassica napus (AACC), a member of the same plant family as Arabidopsis.ResultsWe have identified six BnFT paralogues from the genome of B. napus and mapped them to six distinct regions, each of which is hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 62 publications
3
78
0
1
Order By: Relevance
“…SMG7b and BnaC9.SMG7c may specifically function in female and male meiotic cell cycle progression, respectively, whereas other homologous BnSMG7 copies may be mainly involved in NMD decay, although they can complement the function of BnaC9.SMG7b to some extent. In polyploid crops, the functional divergence of duplicated genes may be an important source of quantitative trait variation, such as the flowering time regulation in B. napus (Wang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…SMG7b and BnaC9.SMG7c may specifically function in female and male meiotic cell cycle progression, respectively, whereas other homologous BnSMG7 copies may be mainly involved in NMD decay, although they can complement the function of BnaC9.SMG7b to some extent. In polyploid crops, the functional divergence of duplicated genes may be an important source of quantitative trait variation, such as the flowering time regulation in B. napus (Wang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…nlm.nih.gov) and a standard BLAST search, some paralogs with very high sequence identity were found. Because homeologs were derived from the same ancestral gene, they are typically highly conserved, as observed for many genes in polyploid species (Wang et al, 2009;Huang and Brûlé-Babel, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Okazaki et al (2007) reported that BoFLC2 plays a central role in the repression of flowering in B. oleracea (Okazaki et al 2007). Wang et al (2009) reported that BnC6FTa, the orthologous gene of BrFTa, was associated with the major QTL for flowering time in B. napus. Furthermore, our QTL analysis showed that BrFTa was located near QTL for bolting time in B. rapa (Fig.…”
Section: Expression Analysis Of Brfta and Brflc2mentioning
confidence: 96%